Effects of contrast medium injection pressure on angiographic image quality - Abosabie, Sara A.; Kao, Tabea; Auer, Timo Alexander; Schnapauff, Dirk; Fehrenbach, Uli; Collettini, Federico; Jonczyk, Martin; Lüdemann, Willie Magnus; Hamm, Charlie Alexander; Wieners, Gero; Schmidt, Robin; Yilmaz, Emine Yaren; et al. (Frontiers in Radiology, 2026)
Rationale and objectivesTo evaluate if higher contrast medium injection pressure can improve image quality of digital subtraction angiography (DSA) in liver-directed interventions.Materials and methodsProspective single-center study including twelve patients with hepatocellular carcinoma (n = 11) or liver metastases (n = 1) undergoing intra-arterial therapies to systematically compare DSA image quality (primary endpoint) and radiation exposure (secondary endpoint) using two microcatheters with maximum application pressures 750 (“C750”) and 1,200 PSI (“C1200”). Patients underwent two DSAs with both microcatheters placed in the common hepatic artery. Application pressure, contrast medium flow, volume, and dose area product were recorded. Image quality was evaluated using a customized questionnaire and quantified by calculating signal- and contrast-to-noise-ratios, and vessel-to-liver signal intensity ratio. Results were compared by paired t-test and Wilcoxon Signed-Rank test.ResultsImage quality using C1200 (achieved 917 ± 94 PSI) was rated more favorably than C750 (731 ± 45 PSI). C1200 reached higher scores of artery visualization in 72% cases, and significantly outperformed C750 regarding tumor blush in 100% (p < 0.001). Contrast-to-noise-ratio were significantly higher in C1200 (p < 0.001) and vessel-to-liver intensity ratios were significantly lower (p = 0.001), both reflecting improved visualization and delineation of liver vessels. Signal-to-noise ratio did not differ significantly. Mean dose area product was comparable (C1200; 371.9 vs. 374.8 μGym2).ConclusionThe results suggest benefits of standardized CM injections for DSA using higher application pressure to enhance image contrast and tumor demarcation during IAT.